(untitled) (Sir Salimullah Medical College Journal, 2026)
The COVID-19 pandemic had given challenges in health systems that placed Bangladesh at a special risk owing to its dense population, absence of adequate laboratories, and excessive volume of patients demanding health services. A number of fluctuations of changes (Alpha, Beta, Delta, and Omicron) in viral variants altered the burden of infectionsand clinical outcomes in the country. Although many constraints in the biosafety and resource issues hadbeen observed, the rapid establishment of RT-PCR testing facilitiesand massive collaboration between the publicand the private sector played major roles in the development of diagnostic services. Bangladesh had made one of the largest vaccination campaigns in South Asia against COVID-19. Vaccine diplomacy had enabled a largedeal of the population to receive immunization which led to fewer cases of severe disease and death. The ongoing emergence of immune-evasive variants highlighted the necessity of genomic surveillance, booster immunization, and persistent public health vigilance. Bangladesh’s experiences showedthat we need strong laboratory systems, research and appropriate communication of scientific information, fair access to vaccines and adequate test facilities to be prepared for future pandemics. In this paper, the authors review the cases of SARS-CoV-2 infectioninBangladesh, introduction of vaccinations and the spread of the disease in the context of global scientific progress. Sir Salimullah Med Coll J 2025; 33: 75-78